Analisis Rasio Solvabilitas dalam Mengukur Kinerja Keuangan Berdasarkan PSAK 401 - Fakhrur Rozi Ramdhani; Mia Lasmi Wardiyah (Akuntansi dan Ekonomi Pajak: Perspektif Global, 2025)
This study aims to analyze the financial performance of Bank Syariah Indonesia (BSI) Bandung Asia Afrika Branch Office using solvency ratios, including Debt to Equity Ratio (DER) and Debt to Asset Ratio (DAR). The research emplyos a descriptive quantitative approach using secondary data obtained from financial reports for the years 2023-2024. Solvency ratios serve as crucial indicators in assessing the bank’s ability to meet long-term obligations and manage its capital structure. The analysis refers to the principles of sharia-based financial reporting as outlined in PSAK 401, which emphasize transparency and accountability. The results show that BSI KC Bandung Asia Afrika experienced improved solvency, as indicated by decreasing DER ratio, along with the presentation of financial statements that comply with Islamic accounting standards.